Modelo de negocio para la implementación de una empresa de consultoría eléctrica en el cantón de Latacunga, Provincia de Cotopaxi. - Medina Pacheco, Mirian Gabriela (2021)
In the present development project, the elaboration of a business model was proposed for the implementation of an electrical consulting company in the Latacunga canton, for which several sources were analyzed in a bibliographical way in relation to the concept of a business model, in The proposal analyzed the target market of the canton, obtaining as a result that 85.4% of potential clients would be willing to acquire our consulting services in maintenance, repair and monitoring in domestic electrical service, it is worth mentioning that users were taken into account. of ELEPCO S.A. from the middle to upper class Latacunga canton for the supply of services; in such a way that marketing strategies based on the 4p's of the marketing mix were proposed, and it was established that the most predominant strategy is that of price, taking into account certain competitors, establishing prices according to the results of the field research, It was determined that the most important value proposal, in addition to the personalized service according to the times and spaces of our clients, is the use of a technological equipment for monitoring, with trained and highly experienced personnel. According to the demand, it was established that the work team will be made up of three people, manager, accountant and electricians who will perform their functions according to each position required by the company. For the fulfillment of the project, the need for investment was $14,354, 36 the same one that settled for $4,354.36 with 32% own capital and $10,000.00 with 68% financed by a financial institution